Wypalenie zawodowe nauczycieli szkół ogólnodostępnych i specjalnych - moderująca rola stresu, radzenia sobie ze stresem oraz poczucia własnej skuteczności - przegląd badań = Professional burnout of mainstream and special education teachers - the moderating role of stress, coping and self-efficacy - a research review - Głowacka, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article was to present research on the issue of professional burnout among teachers, taking into account the division into teachers of special and general schools. In addition, research on psychological variables that may correlate with professional burnout among teachers was reviewed: stress, coping with stress and self-efficacy. Analyzing the results of the research, it was possible to confirm that teachers and teachers of special and mainstream schools are a professional group affected by professional burnout. It was also possible to show several factors influencing the level of stress in teachers. Teachers in the presented research most often used task oriented and avoidance oriented styles of coping with stress. A partial correlation between the type of school and the style of coping with stress was found. It was also possible to show a partial correlation between occupational burnout and stress, occupational burnout and self-efficacy, and a partial correlation between all three factors.
Keywords: wypalenie zawodowe; radzenie sobie ze stresem; samoskuteczność; nauczyciele; edukacja specjalna; professional burnout; coping wih stress; self-efficacy; teacher; special education